The Influence of Emotional Intelligence and Organizational Commitment on Employee Performance at the Department of Labor and Transmigration of Seluma Regency - Lina Yuniarti; Ermy Wijaya; Yesi Indian Ariska (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the influence of emotional intelligence and organizational commitment on employees’ performance at the Department of Labor and Transmigration of Seluma Regency. The sample in this study was 52 employees at the Department of Labor and Transmigration of Seluma Regency. The data was collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. The results of multiple regressions show that the equation Y = 6.045 + 0.419 X1 + 0.458 X2. The result of regression direction is positive, meaning that the higher emotional intelligence and organizational commitment variables, the higher the employees’ performance will also be. The value of the coefficient of determination is 0.595. This means that X1 (emotional intelligence) and X2 (organizational commitment) have a contribution to performance (Y) of 59.5% while the remaining 40.5% is influenced by other variables not examined in this study. Overall, the results t test has a significant value is less than 0.05, so it can be interpreted that X1 (emotional intelligence) and X2 (organizational commitment) have a significant influence on performance (Y) partially or individually. The results of the F test have a significant value of 0.000 < 0 ,05. Because the level of significance below 0.05 indicates that X1 (emotional intelligence) and X2 (organizational commitment) have a significant influence on performance (Y).